Religiosität türkischer Migranten im Generationenverlauf: ein Befund und einige Erklärungsversuche = Religiosity of first and second generation Turkish migrants : a phenomenon and some attempts at a theoretical explanation - Diehl, Claudia; Koenig, Matthias (Zeitschrift für Soziologie, 2009)
Intergenerational stability of the religiosity of Turkish migrants is surprisingly high. In this article, several theoretical explanations for the maintenance of religiosity from generation to generation are presented and tested empirically against data from the German Generations- and Gender Surveys. We can show that classical versions of assimilation theories, concepts of symbolic religiosity, of religiosity as a compensation for a lack of social status, or of a high intergenerational stability of values in general cannot fully explain this phenomenon. Religiosity does not decline between the first and the second generation, nor does it become more symbolic in character. Furthermore, empirical evidence yields only limited support for the hypothesis that high levels of individual religiosity can only be found among structurally and socially less assimilated segments of the immigrant population. The same holds true for the argument that they just reflect generally high intergenerational value stability among immigrants. Concequently, in the final section we discuss the role of contextual factors in explaining intergenerational stability in migrants’ religiosity such as an increasing diversity of the religious Islamic field or the salience religion as a symbolic boundary marker between natives and migrants.
Gesehen am 08.06.2021